Author Correction: ALF: a strategy for identification of unauthorized GMOs in complex mixtures by a GW-NGS method and dedicated bioinformatics analysis. Issue 1 (December 2018) - Košir, Alexandra; Arulandhu, Alfred; Voorhuijzen, Marleen; Xiao, Hongmei; Hagelaar, Rico; Staats, Martijn; Costessi, Adalberto; Žel, Jana; Kok, Esther; van Dijk, Jeroen
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.